Diagnosis and Treatment of Intussusception in a Cow - Dabak, Murat; Ünsaldi, Emine; Gül, Yusuf (My University, 2001)
An 8-year-old cow admitted to the Veterinary Faculty, Internal Medicine Clinic (University of Firat, Elazi?/TURKEY), was diagnosed with intussusception, and the diagnosis was confirmed by experimental laparotomy. Intussusception was corrected by enterectomy and intestinal anastomosis. Defecation on the day following the operation indicated normal intestinal flow. The animal was kept under observation for ten days after the operation, and had a full recovery.
Bir İnekte Tespit Edilen Ba?irsak İnvaginasyonu ve Sa?altimi
Keywords: Cattle; Diagnose; Intussusception; Treatment